LIFE CARE PLANNING AND CASE MANAGEMENT ACROSS THE LIFESPAN - Rutherford-Owen, Tanya; Barros-Bailey, Mary; Weed, Roger O. ([S.l.] : ROUTLEDGE, 2023)
Celebrating 25 years since its first publication, the fifth edition of this best-selling text is the most up-to-date and complete resource available on what a life care planner does, how the life care planner does it, and issues that affect the day-to-day role of a life care planner. Now featuring new material on pediatric life care planning and case management, including brachial plexus injuries and neurodevelopmental disorders, this new edition provides guidance and planning for cases across the lifespan. It begins with a series of chapters examiningten different professional specializations that often contribute to a life care plan, before providing critical information for developing life care plans for individuals with different physical, mental, and cognitive conditions including spinal cord injury, brain injury, and chronic pain. Uniquely comprehensive, the book also includes chapters on the forensic and legal context of life care planning, as well as equipment/technology, evidence-based literature/resources, and special education/special needs planning relevant to pediatric life care planning. Also including chapters dedicated to life care planning methodology and life care planning research, this is an essential resource for anyone practicing or studying life care planning or managing the needs of those requiring chronic medical care over the lifespan.
Revised edition of: Life care planning and case management handbook / edited by Debra Berens and Roger Weed. Fourth edition. 2018.
Keywords: MEDICAL / Allied Health Services / General; MEDICAL / Health Care Delivery; MEDICAL / Nursing / General; Life care planning